Interactive Effects of Phosphorus Fertilization and Atonic Application on Growth, Productivity, and Phosphorus-Use Efficiency Roselle (Hibiscus sabdariffa L.) - Al-Hamdany, Heba M. M. (American Journal of Botany and Bioengineering, 2026)
A pot experiment was conducted during the 2023-2024 growing season at the College of Medicinal and Industrial Plants, Kirkuk University, in the Ronaki area of ​​the Kirkuk Governorate, to study the interaction between phosphorus levels and the growth regulator Atonic on the growth, productivity, and phosphorus use efficiency of the Roselle plant. The experiment was carried out according to a randomized complete block design with three replications. The treatments consisted of four phosphorus fertilizer rates (0, 25, 50, and 75 kg P2O5 ha-1) and three Atonic levels (0, 100, and 150 mg L-1). The traits studied included plant height, number of branches plant-1, chlorophyll content, leaf area, dry weight, nitrogen, phosphorus, and potassium concentrations, total yield, and phosphorus use efficiency. The results showed that phosphate fertilization had a significant effect on most of the studied traits. The 50 kg P2O5 ha-1 level achieved the highest values ​​in plant height (78. 10 cm), number of branches/plant (9.2), chlorophyll content (8. 81 mg g-1), leaf area Plant (1. 80 m2), plant dry weight (218. 00 g plant-1), nitrogen concentration (2.70%), phosphorus concentration (0. 32%), potassium concentration (2. 65%), yield (3330. 95 kg ha-1), and phosphorus –use efficiency (198. 64%). The highest phosphorus rate (75 kg P2O5 ha-1) adversely affected all the studied traits. As for the Atonic effect, the 150 mg L-1 level had a significant effect on all the studied traits. It produced plant height (77. 07 cm), number of branches/plant (8.9), chlorophyll content (8. 98 mg g- 1 fresh weight), leaf area index (2.07 m2), dry weight (227. 26 g plant- 1), nitrogen concentration (3. 09%), phosphorus concentration (0. 30%), potassium concentration (2.59%), yield (2973. 80 kg ha-1), and fertilization efficiency (166. 62%), the interaction effect showed that the A 2 B 2 combination gave the highest growth and yield indicators for the Roselle plant. Accordingly, the study recommends using phosphate fertilization at a rate of 50 kg P2 O5 ha-1 and spraying with Atonic at a concentration of 150 mg L⁻1 to achieve optimal growth and productivity of the roselle plant under calcareous soil conditions.